Identification of Patient Factors Associated with Loss to Follow-Up at 1-Year Post Transcatheter Aortic Valve Replacement. Issue 1 (2nd January 2019) - Wooley, Jordan R.; Vasudevan, Anupama; Tabachnick, Deborah; Squiers, John J.; DiMaio, J. Michael; Mack, Michael J.; Holper, Elizabeth
ABSTRACT: Background: Centers for Medicare and Medicaid Services requires for payment that transcatheter aortic valve replacement (TAVR) programs follow patients for at least 1-year post-procedurally and record outcomes in a data registry. We sought to identify which patient factors are associated with loss to follow-up 1 year after TAVR. Methods: A retrospective study of 604 TAVR patients between January 2012 and April 2017 was conducted. Patients who suffered 1-year mortality (n = 67) were excluded. A step-wise logistic regression analysis was employed to identify risk factors associated with loss to follow-up 1 year after TAVR. Discriminatory ability and calibrating efficiency of the final model was assessed using receiver operating curve analysis and Hosmer-Lemeshow (HL) goodness-of-fit test, respectively. Results: A total of 537 patients met inclusion criteria, with median age 82 years (range, 47–100) and 279 (51.9%) females. There were 79 (14.7%) patients without 1-year follow-up. After multivariable analysis, general anesthesia (OR 6.25, 95%CI 2.15–18.18), failure of the 5-meter walk test preoperatively (OR 2.73, 95%CI 1.31–5.7), any post-procedural complication (OR 1.81, 95%CI 1.08–3.03), distance in miles (for every 100 miles) between home address and hospital (OR 1.3, 95%CI 1.1–1.5) were predictive of loss to follow-up at 1 year. Higher albumin levels (OR 0.54, 95%CI 0.33–0.88) were protective against becoming lost to follow-up at 1 year. The area under the curve was 0.73 and the HL was p = 0.75. Conclusions: Multiple factors are predictive of loss to follow-up at 1 year after TAVR. Although few factors are readily modifiable, they can be used to identify patients at increased risk for loss to follow-up after TAVR.